Morpholino‐induced exon skipping stimulates cell‐mediated and humoral responses to dystrophin in mdx mice. Issue 3 (16th April 2019) - Vila, Maria C; Novak, James S; Benny Klimek, Margaret; Li, Ning; Morales, Melissa; Fritz, Alexander G; Edwards, Katie; Boehler, Jessica F; Hogarth, Marshall W; Kinder, Travis B; Zhang, Aiping; Mazala, Davi; et al.
Abstract: Exon skipping is a promising genetic therapeutic strategy for restoring dystrophin expression in the treatment of Duchenne muscular dystrophy (DMD). The potential for newly synthesized dystrophin to trigger an immune response in DMD patients, however, is not well established. We have evaluated the effect of chronic phosphorodiamidate morpholino oligomer (PMO) treatment on skeletal muscle pathology and asked whether sustained dystrophin expression elicits a dystrophin‐specific autoimmune response. Here, two independent cohorts of dystrophic mdx mice were treated chronically with either 800 mg/kg/month PMO for 6 months ( n  = 8) or 100 mg/kg/week PMO for 12 weeks ( n  = 11). We found that significant muscle inflammation persisted after exon skipping in skeletal muscle. Evaluation of humoral responses showed serum‐circulating antibodies directed against de novo dystrophin in a subset of mice, as assessed both by Western blotting and immunofluorescent staining; however, no dystrophin‐specific antibodies were observed in the control saline‐treated mdx cohorts ( n  = 8) or in aged (12‐month‐old) mdx mice with expanded 'revertant' dystrophin‐expressing fibers. Reactive antibodies recognized both full‐length and truncated exon‐skipped dystrophin isoforms in mouse skeletal muscle. We found more antigen‐specific T‐cell cytokine responses (e.g. IFN‐g, IL‐2) in dystrophin antibody‐positive mice than in dystrophin antibody‐negative mice. We also found expression of major histocompatibility complex class I on some of the dystrophin‐expressing fibers along with CD8+ and perforin‐positive T cells in the vicinity, suggesting an activation of cell‐mediated damage had occurred in the muscle. Evaluation of complement membrane attack complex (MAC) deposition on the muscle fibers further revealed lower MAC deposition on muscle fibers of dystrophin antibody‐negative mice than on those of dystrophin antibody‐positive mice. Our results indicate that de novo dystrophin expression after exon skipping can trigger both cell‐mediated and humoral immune responses in mdx mice. Our data highlights the need to further investigate the autoimmune response and its long‐term consequences after exon‐skipping therapy. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.